IMPLICATIONS OF PRICE CONSCIOUSNESS AND PRODUCT QUALITY ON IPHONE USERS' PURCHASE INTENTION: THE ROLE OF SALE PRONENESS AS A MEDIATION FACTOR - Thoriqotul A'iniyah; Wismantoro, Yohan; Mahmud, Mahmud; Pakarti, Piji (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2025)
The iPhone is a premium smartphone product that has a higher price than competing brands So not everyone can afford it. Therefore, someone who wants to use an iPhone can find ways to get the product at a cheaper price. This study was conducted to determine the extent to which price consciousness and product quality contribute to purchase intentions, as well as the role of sale proneness as a mediating variable. The objects of this study are Generation Z and Millennials who have an interest in the old version of the iPhone. With sample criteria: consumers who buy their own iPhone, live in Semarang City, and are aged 17-44 years. The method used in this study is quantitative, with data collection carried out through questionnaires answered by 144 respondents. The analytical tool used in this study is SmartPLS software. The results of this study indicate that price consciousness has a positive and significant effect on sale proneness. In addition, product quality is also proven to have a positive and significant effect on sale proneness. Furthermore, both price consciousness and product quality have a positive and significant effect on purchase intention. Meanwhile, sale proneness also has a positive and significant effect on purchase intention. These findings indicate that both price consciousness, product quality, and sale proneness play an important role in shaping consumer purchase intention.